Optimizing the lung cancer screening interval: the world is waiting - Ridge, Carole A.; Boiselle, Phillip M. (Journal of Thoracic Disease, 2016)
Although lung cancer is the leading cause of cancer death throughout the world, until recently, there has not been an accepted screening test for this deadly disease. Fortunately, the National Lung Screening Trial (NLST) has now shown that screening with low dose computed tomography (CT) can reduce lung cancer-specific mortality by 20% compared to chest radiography (1). This test thus has the potential to substantially reduce lung cancer deaths throughout the world.